ChemInform Abstract: Regioselective Friedel—Crafts Reaction of Electron‐Rich Benzenoid Arenes and Spiroepoxyoxindole at the Spiro‐Center: Efficient Synthesis of Benzofuroindolines and 2H‐Spiro[benzofuran]‐3, 3′‐oxindoles. Issue 49 (17th November 2016) - Hajra, Saumen; Maity, Subrata; Roy, Sayan
Abstract: About 30 derivatives such as (III) and (VI) are prepared from spiroepoxyindoles and phenolic reactants.